A prospective study to determine the predictive ability of hypertensive disorders during pregnancy-gestosis score for the development of pre-eclampsia - Reddy, Pavithra; Indrani, Chaitanya; Vydyanath, Vandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Hypertensive disorders during pregnancy (HDP)-gestosis score is a risk scoring system (score 1-3) for the development of pre-eclampsia. When a pregnant woman’s total score is equal to or greater than 3, she is labelled as “at risk for pre-eclampsia” and is managed accordingly. Objectives were to determine the sensitivity, specificity, and diagnostic accuracy of HDP-gestosis score for predicting pre-eclampsia (PE). Methods: This prospective study included 100 pregnant women who presented at the department of obstetrics and gynaecology. After 20 weeks of pregnancy, the patients were assessed for the development of pre-eclampsia. Details of age, gravida, obstetric history, menstrual cycle regularity, polycystic ovarian disease history, duration of marriage, parity, past medical and surgical intervention, previous/present medication, and family history were taken. Gestosis score was calculated and classified into mild (score of 1), moderate (score of 2) and high risk (score of ≥ 3) for the development of PE. Sensitivity, specificity, and diagnostic accuracy of HDP-gestosis score for predicting the development of PE were determined. Results: The mean age, gestational age, and body mass index (BMI) of the women were 28.4±6.8 years, 11.5±2.04 weeks, and 24.5±3.7 kg/m2, respectively. The gestosis score was 2 in 43.13% of the participants, 1 in 42.28%, and ≥3 in 14.59% of the women. PE developed in 15.01% (n=71) participants. The sensitivity, specificity, PPV, NPV, and diagnostic accuracy of HDP-gestosis score for predicting PE were 83.1%, 97.51%, 85.51%, 97.03% and 95.35%, respectively. Conclusions: Gestosis score is a novel early marker for prediction of the development of PE allowing for a prompt management for the patients, thereby curbing the adverse consequences.